Reducing the psychological distress of family caregivers of home based palliative care patients: Longer term effects from a randomised controlled trial - Hudson, P.; Trauer, T.; Kelly, B.; O'Connor, Moira; Thomas, K.; Zordan, R.; Summers, M. (John Wiley and Sons Ltd, 2015)
Psycho-Oncology published by John Wiley & Sons Ltd. Background: Palliative care incorporates comprehensive support of family caregivers because many of them experience burden and distress. However, evidence-based support initiatives are few. Purpose: We evaluated a one-to-one psychoeducational intervention aimed at mitigating the distress of caregivers of patients with advanced cancer receiving home-based palliative care. We hypothesised that caregivers would report decreased distress as assessed by the General Health Questionnaire (GHQ). Method: A randomised controlled trial comparing two versions of the delivery of the intervention (one face-to-face home visit plus telephone calls versus two visits) plus standard care to a control group (standard care only) across four sites in Australia. Results: Recruitment to the one visit condition was 57, the two visit condition 93, and the control 148. We previously reported non-signi fi cant changes in distress between times 1 (baseline) and 2 (1-week post-intervention) but signifi cant gains in competence and preparedness. We report here changes in distress between times 1 and 3 (8-week post-death). There was significantly less worsening in distress between times 1 and 3 in the one visit intervention group than in the control group; however, no significant difference was found between the two visit intervention and the control group. Conclusions: These results are consistent with the aim of the intervention, and they support existing evidence demonstrating that relatively short psychoeducational interventions can help family caregivers who are supporting a dying relative. The sustained benefit during the bereavement period may also have positive resource implications, which should be the subject of future inquiry.